Adaptation Strategies of Sitiarjo Villagers in Water Supply and Sanitation to Face The Health Impacts of Floods - Suliono Suliono (JURNAL KESEHATAN LINGKUNGAN, 2018)
One of the impacts of climate change is the increasing frequency of flood disaster in Sitiarjo Village, Malang Regency. In recent years, the impact of floods in the form of emerging and rising infectious diseases has been suppressed.. Adaptation strategies implemented in disaster management are thought to be influential factors in the success of disaster risk reduction.This study aims to examine in depth the pattern of adaptation applied in the cycle of disaster management in Sitiarjo Village. This study aims to examine in depth the adaptation strategy adopted in the cycle of disaster management in Sitiarjo Village. The research method is qualitative with case study approach. The subjects of research are the elements directly involved in disaster management consisting of Puskesmas Health Workforce, Village Government Officer, Disaster Volunteer, and Community.The results show that the community adaptation strategy has been running well in the context of disaster preparedness which includes: modification of house design, supply of drinking water and clean water, closet closure and air pit in latrines. While in the context of emergency response, each sector has taken the necessary tasks such as medical action and quality recovery of dug wells.The duties of disaster volunteers such as SIBAT and SBH are very important in empowering the community to create a resilient community.There is still a gap in access to information and tools for the recovery of dug wells in some areas.The conclusion that can be drawn is that most people have adopted a good adaptation strategy in the field of water supply and sanitation to face the health impact of flood disaster. To improve the quality of disaster management still needed additional materials and supporting equipment for Puskesmas and community, and capacity building for disaster volunteers.